International economics : - Krugman, Paul R. (HarperCollins College Publishers, 1994)
Using a step-by-step approach, the text builds a unified framework international economics. It includes three new chapters covering regional economic issues (including location theory), optimum currency areas and the European Community, and the problems of former communist countries in the transition to a market economy. Topical new applications include the US oilseed dispute with Europe, the BCCI scandal, Third-World debt forgiveness and "1980-1993 - disinflation, recovery and the global slump".